Penerapan Strategi Pembelajaran pada Mata Pelajaran PAI di SDN Cikokol 3 Kota Tangerang - Suhaibah, Euis; Erika, Siti Anisa; Magdalena, Ina (Lembaga Yasin AlSys, 2022)
This study aims to determine the learning strategies used by teachers, especially PAI teachers at SDN Cikokol 3 Tangerang City. Knowing how PAI teachers apply learning strategies to students. The process used on this occasion are interview and documentation techniques. The learning strategies used by PAI teachers generally apply expository learning strategies. and demonstrations. With the learning and learning strategy, it is hoped that the learning and learning process will run well so that it can improve student achievement and have behavior that is in accordance with the teachings of their religion.